Ethos, Paradigm, and the 'Middle Science Trap': R&D&B in Vietnamese Higher Education Institutions - Ngoc Hung, Le (VNU Journal of Science: Education Research, 2025)
The opening section of this paper provides a research overview, focusing on two key theoretical frameworks: Robert Merton’s sociological theory of science - particularly his concept of the “ethos of science” - and Thomas Kuhn’s epistemology of science, with an emphasis on the concepts of paradigm and scientific revolution. These two approaches are used to identify and explain the phenomenon of the “Middle Science Trap” - a condition in which a small minority of researchers produce the majority of scientific publications, especially those in “reputable international journals”, while most research activity remains in the transition from pre-paradigm to paradigm period within the process of scientific development. The subsequent section presents the results of a case study on “Scientific Research Methodology” and “Sociological Research Methods.” The aim of this section is to clarify the urgency and feasibility of educating students about the ethos and paradigms of modern science for conducting R&D&B (short for Research & Development & Business) activities, in order to both avoid falling into the “Middle Science Trap” and foster breakthrough scientific development that contributes to higher education reform toward rapid and sustainable development. R&D&B education reflects the integration of scientific research, technological development, and entrepreneurial spirit. This model needs to be effectively implemented in the training and scientific research of students at Vietnamese higher education institutions, with the goal of promoting applied research and building a learning environment closely linked to innovation.